Does participation mean reciprocal learning? The relationships between diverse stakeholders during participatory budgeting in Paris. Issue 3 (2nd July 2016) - Nez, Héloïse
ABSTRACT: This article analyses the process by which lay citizens acquire new knowledge through participation and, reciprocally, how elected officials, civil servants, and associative leaders may learn from lay citizens. The aim is to develop a better understanding of the relationships and dynamics between these different stakeholders since the turn towards participatory democracy. Participatory devices generate new dynamics among social movements' actors and the creation of knowledge stemming from interactions between participants, who all learn from each other. Nevertheless, these mutual forms of learning do not necessarily imply the disappearance of power relations and knowledge imposition attempts by dominant stakeholders during the debates.